Spatial quantification and economic valuation of recreational ecosystem services in Iran’s Zagros Mountains: A sub-watershed analysis using the Recreation Opportunity Spectrum (ROS) framework - Mohammadyari, Fatemeh; Abdollahi, Khodayar; Tumelienė, Eglė; Birvydienė, Rosita (International Conference “Environmental Engineering”, 2026)
Recreational Ecosystem Services (RES) deliver critical non-material benefits, yet their spatially explicit valuation remains underexplored in the data-limited, mountainous landscapes of the Middle East. This study addresses this gap by presenting the first sub-watershed-level quantification and economic valuation of RES across the 20 hydrological sub-units of Chaharmahal-Bakhtiari Province, Iran a core part of the biodiverse central Zagros Mountains. We operationalize the Recreation Opportunity Spectrum (ROS) framework by integrating biophysical supply indicators (naturalness, protected area status, and hydrological attraction) with accessibility metrics (distance to settlements and roads) to derive a continuous Recreational Supply Index (RSI). Economic valuation was conducted via benefit transfer, using an inflation-adjusted (2011→2024, CPI-based) willingness-to-pay value from Zagros forests). The total annual RES value for the province is estimated at IRR 113.86 trillion (≈ USD 268 million at the 2024 official market exchange rate of IRR 425,000/USD), with a mean per-hectare value of IRR 69.39 million. Hotspots (sub-watersheds 5, 6, and 20) coincide with intact Quercus brantii forests and moderate-to-high remoteness, whereas eastern sub-watersheds show degraded recreational capacity due to agricultural expansion and urban encroachment. Our findings demonstrate that conserving Zagros woodlands concurrently sustains biodiversity, hydrological function, and cultural services providing a robust, transferable methodology for ecosystem accounting and spatial planning in socio-ecologically comparable regions.